Selective Nanotrench Filling by One‐Pot Electroclick Self‐Constructed Nanoparticle Films. Issue 36 (19th June 2015) - Rydzek, Gaulthier; Toulemon, Delphine; Garofalo, Antonio; Leuvrey, Cedric; Dayen, Jean‐François; Felder‐Flesch, Delphine; Schaaf, Pierre; Jierry, Loïc; Begin‐Colin, Sylvie; Pichon, Benoît P.; Boulmedais, Fouzia
<x xml:space="preserve">Abstract</x> Integration of nanoparticles (NPs) into nanodevices is a challenge for enhanced sensor development. Using NPs as building blocks, a bottom‐up approach based on one‐pot morphogen‐driven electroclick chemistry is reported to self‐construct dense and robust conductive Fe3O4 NP films. Deposited covalent NP assemblies establish an electrical connection between two gold electrodes separated by a 100 nm‐wide nanotrench.